Relative deprivation between neighbouring wards is predictive of coronary heart disease mortality after adjustment for absolute deprivation of wards. Issue 9 (28th June 2011) - Allender, Steven; Scarborough, Peter; Keegan, Thomas; Rayner, Mike
Abstract : Background: The aims of this study were to assess whether deprivation inequality at small area level in England is associated with coronary heart disease (CHD) mortality rates and to assess whether this provides evidence of an association between area-level and individual-level risk. Methods: Mortality rates for all wards in England were calculated using all CHD deaths between 2001 and 2006. Ward-level deprivation was measured using the Carstairs Index. Deprivation inequality within local authorities (LAs) was measured by the IQR of deprivation for wards within the LA. Relative deprivation for wards was measured as the modulus of the difference between deprivation for the ward and average deprivation for all neighbouring wards. Results: Deprivation inequality within LAs was positively associated with CHD mortality rates per 100 000 (eg, all men β; 95% CI=2.7; 1.1 to 4.3) after adjustment for absolute deprivation (p<0.001 for all models). Relative deprivation for wards was positively associated with CHD mortality rates per 100 000 (eg, all men 1.4; 0.7 to 2.1) after adjustment for absolute deprivation (p<0.001 for all models). Subgroup analyses showed that relative deprivation was independently associated with CHD mortality rates in both affluent and deprived wards. Conclusions: Rich wards surrounded by poor areas have higher CHD mortality rates than rich wards surrounded by rich areas, and poor wards surrounded by rich areas have worse CHD mortality rates than poor wards surrounded by poor areas. Local deprivation inequality has a similar adverse impact on both rich and poor areas, supporting the hypothesis that income inequality of an area has an impact on individual-level health outcomes.